Development of broad‐spectrum bacterial blight resistance into thermo‐sensitive genic male sterile lines. Issue 1 (27th November 2015) - Jiang, Jiefeng; Mi, Jiaming; Ali, Jauhar; Mou, Tongmin
Abstract: Two‐line hybrid rice technology is an effective way to increase rice production and improve rice quality. In this study, three bacterial blight (BB) resistance genes, Xa7, Xa21 and Xa23, were introgressed separately into C815S, a popular thermo‐sensitive genic male sterile (TGMS) line to develop five BB‐resistant lines (Hua1005S, Hua1002S, Hua1009S, Hua1006S and Hua1001S) to be resistant against seven races of Xanthomonas oryzae pv. oryzae ( Xoo ). The two‐line hybrids with heterozygous Xa23 were resistant against seven Xoo strains. But, the hybrids with heterozygous loci for both Xa7 and Xa21 were only resistant against three Xoo strains and were moderately susceptible to the other four strains indicating the role of modifiers influencing the poor expression of dominant BB resistance genes under heterozygous state. Among them, Hua1006S was found to be a promising TGMS line with its higher degree of disease resistance level on account of broad‐spectrum resistance gene Xa23 besides possessing better plant type and rice grain quality features.